Sledge Hammer! : Season Two Disc 1-2 - Coolidge, Martha; Morris, Leslie; Kurt Paul; Patti Tippo See more (Starz / Anchor Bay, 1986)
"HAMMERED: The Best of Sledge" (Laserdisc) - Prepare yourself for four crime stories that pack more punch than Sledge Hammer's trusty Magnum. And loaded with more misadventure than there is air between Sledge's ears. Our hero find himself up against the likes of the infamous Elvis impersonator serial killer, a powerful Mafioso Don, the sex-starved Elizabeth, and a violent revolutionary. Armed only with a Magnum, grenades, several Uzi machine-guns, and a bazooka, our hero singlehandedly makes the streets safe again for law-abiding citizens.
It would take more than a nuclear explosion to stop everyone's favorite violence-loving lawman! David Rasche returned-along with co-stars Anne-Marie Martin and Harrison Page-in the surprising second season of the series that Entertainment Weekly calls "absolutely hilarious" These are the infamous final episodes featuring such guest stars as Richard Moll, Ray Walston, Edy Williams, Bud Cort, Bernie Kopell, Adam Ant, Davy Jones and more, in the "sitcom for people who hate sitcoms" that remains one of the most dangerously funny shows in TV history.
Language: English Subtitle: ''No Subtitle"
Keywords: Comedy; TV Series